Regime changes in sub-prime margins under the US housing bubble (2009)
Risk-based pricing is an alignment of loan risk pricing with expected loan risk – charging a higher interest rate for higher risk (Yezer, 2002). This article shows systematic relaxation of risk pricing for sub-prime loans during the US housing bubble, a period that extended from 2001 to 2006. For example, an identical loan, but having different vintages is shown to have significantly lower premiums in 2005 than in 2003. Strikingly, for a given credit risk, estimation results show a premium reduction of 60 basis points in sub-prime originations from 2003 to 2005.